2023
DOI: 10.1097/icb.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive Recurrence of Intraocular Lymphoma Despite Chimeric Antigen Receptor T-Cell Therapy

Abstract: Purpose: To present the first reported case of presumptive intraocular recurrence of lymphoma following Chimeric Antigen Receptor (CAR) T-cell therapy despite systemic control by CD19-CAR T cells.Methods: Observational case report.Results: A 59-year-old man with diffuse, large, B-cell lymphoma subsequently developed secondary central nervous system disease despite chemotherapy. He underwent stem cell transplantation but relapsed again and was scheduled to receive CAR T-cell therapy. He developed vitritis sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A total of 27 ocular AEs were documented in the reviewed cases (Figure 1). 6,[8][9][10][12][13][14][15] The most common AEs were blurred vision with 10 reports, retinal disease with 5 reports, and floaters with 4 reports (Table 2. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 27 ocular AEs were documented in the reviewed cases (Figure 1). 6,[8][9][10][12][13][14][15] The most common AEs were blurred vision with 10 reports, retinal disease with 5 reports, and floaters with 4 reports (Table 2. ).…”
Section: Resultsmentioning
confidence: 99%
“…Of particular concern is an AE shared by Denton et al, Khanna et al, and Zu et al wherein their patients exhibited retinal detachment, hypothesized to be a consequence of CAR T‐cell expansion and cytokine release 8,13,15 . Three intriguing cases reported by Willier et al, Abou‐Samra et al, and Taher et al were instances of ocular recurrence after CAR‐T cell therapy, including a case of acute lymphoblastic leukemia and two of diffuse large B‐cell lymphoma 6,10,14 . It is worth mentioning that the FAERS database reported one case ocular lymphoma for tisagenlecleucel (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports have brought attention to the recurrence of hematological malignancies within the eye following CD19 CAR-T-cell therapy, despite successful control of the central nervous system and the rest of the body 35 , 36 , 45 . It is suggested that insufficient anti-CD19 CAR-T cells may enter the eye, allowing neoplastic B cells to persist.…”
Section: Ocular Adverse Events In Chimeric Antigen Receptor T-cell Th...mentioning
confidence: 99%